Aleksei P. Okladnikov : the great explorer of the past.: the great explorer of the past. A biography of a Soviet archaeologist (1900s - 1950s) / Volume I, (2019) - Konopat︠s︡kiĭ, Aleksandr Kirillovich
No abstract available